2011
DOI: 10.1007/s10529-011-0724-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a secretory β-glucosidase from Trichoderma reesei in Pichia pastoris and its characterization

Abstract: A β-glucosidase gene (bglI) from Trichoderma reesei was cloned into the pPIC9 vector and integrated into the genome of Pichia pastoris GS115. Under the control of the methanol-inducible alcohol oxidase (AOX) promoter and using Saccharomyces cerevisiae secretory signal peptide (α-factor), the recombinant β-glucosidase was expressed and secreted into the culture medium. The maximum recombinant β-glucosidase activity achieved was 60 U/ml, and β-glucosidase expression reached 0.3 mg/ml. The recombinant 76 kDa β-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…Number of β-glucosidase genes from bacteria, yeast and fungi have been cloned and expressed in E. coli and eukaryotic systems such as Saccharomyces cerevisiae, Pichia pastoris, and T. reesei [168,180,181,182]. Cloning and expression has started with either 1) genomic DNA digestion, construction of genomic DNA library and then functional screening for β-glucosidase [183], or 2) construction of cDNA library and function-based screening of β-glucosidase [169,184].…”
Section: Cloning and Expression Of Microbial β-Glucosidasesmentioning
confidence: 99%
“…Number of β-glucosidase genes from bacteria, yeast and fungi have been cloned and expressed in E. coli and eukaryotic systems such as Saccharomyces cerevisiae, Pichia pastoris, and T. reesei [168,180,181,182]. Cloning and expression has started with either 1) genomic DNA digestion, construction of genomic DNA library and then functional screening for β-glucosidase [183], or 2) construction of cDNA library and function-based screening of β-glucosidase [169,184].…”
Section: Cloning and Expression Of Microbial β-Glucosidasesmentioning
confidence: 99%
“…Gupta with coauthors [11] found efficient extracellular secretion of a β glucosidase fused with the hyperosmotically induc ible periplasmic protein, OsmY, in E. coli and exhibited 2.2 U/mL of β glucosidase activity in the extracellular fraction at 16 h post induction. Chen et al [12] reported expression of a secretory β glucosidase from Trichoderma reesei in P. pastoris that the maximum recombinant β glucosidase activity achieved 60 U/mL. Mendoza Aguayo with coworkers [13] revealed extra cellular expression of β glucosidase of Cellulomonas fla vigena PN 120 in the supernatant of a rich medium showing 582 U/L.…”
mentioning
confidence: 99%
“…Based on the diversity in substrate specificity, β-glucosidases have been classified into aryl β-glucosidases that only hydrolyze p-nitrophenyl-β-D-glucopyranoside (pNPG), cellobiase or alkyl β-glucosidases that specifically hydrolyze cello-oligosaccharides (including cellobiose), and broad substrate spectrum β-glucosidases having activity towards both substrates mentioned above [3]. To date, a number of GH3 β-glucosidase genes have been isolated and characterized from different fungi, such as Aspergillus fumigatus [9], Penicillium piceum [10], and Trichoderma reesei [11]. Recently, β-glucosidases from thermophilic fungi have attracted much attention due to its potential applications associated with their inherent biochemical properties like good stability [12].…”
mentioning
confidence: 99%